ANALISIS PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA SEKTOR KONSTRUKSI SEBAGAI BAGIAN DARI SDGS 8: PEKERJAAN LAYAK DAN PERTUMBUHAN EKONOMI - Delanaira Asyifa Amodia; Faiz Satria Sasongko; Finsen Setiawan; Fazli Rafa Amin; Agnia Qurrota Aini (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Occupational Safety and Health (OSH) is a key component in supporting Sustainable Development Goal (SDG) 8 related to decent work. However, small and medium-scale construction projects in Indonesia still show low levels of OSH compliance. This study aims to evaluate the dominant factors that influence OSH compliance in construction projects through field observations, in-depth interviews with workers, and analysis of priority issues using a four-criteria weighting scheme. The results of the study show three main problems, namely low awareness of the use of personal protective equipment (PPE/APD), negligence in the use of work tools, and a lack of safety signs. These three factors were consistently repeated across all observation sites and were the main causes of increased occupational accident risks. In response to these findings, this study developed a solution concept using the SCAMPER method to formulate more functional and adaptive PPE/APD innovations. This approach emphasizes that improving safety requires more than just providing PPE/APD; it also requires more ergonomic designs, continuous education, and the strengthening of a safety culture at the operational level. This study contributes by mapping the root causes of OSH issues in small-to-medium construction projects while offering directions for innovation that can strengthen the implementation of decent work in line with SDG 8.